Coordination changes in front-crawl swimming. (6th May 2020) - Carmigniani, R.; Seifert, L.; Chollet, D.; Clanet, C.
Abstract : We report the evolution of the coordination with velocity in front-crawl swimming which is used in competitions over a large range of distances (from 50 m up to 25 km in open-water races). Inside this single stroke, top-level swimmers show different patterns of arm organization. At low velocities, swimmers select an alternated stroke with gliding pauses during their propulsion. The relative duration of the gliding pauses on a stroke cycle is independent of the velocity in this first regime. Above a critical velocity, the relative duration of the gliding pauses starts to decrease as speed increases. Above a second critical velocity, the gliding pauses disappear and the swimmers start to superpose their propulsion phases. These three regimes are first revealed experimentally and then studied theoretically. It appears that below the first critical velocity, swimmers use a constant coordination index and vary their speed by varying their propulsive force to minimize their cost of propulsion. For larger velocities, swimmers use their maximum propulsive force and vary their recovery time to increase further their speed. The physical model developed is general and could be applied to understand other modes of locomotion.